2013
DOI: 10.1007/s10059-013-0030-0
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Indehiscence Caused by Enhanced Expression of NO TRANSMITTING TRACT in Arabidopsis thaliana

Abstract: In flowering plants, fruit dehiscence enables seed dispersal. Here we report that ntt-3D, an activation tagged allele of NO TRANSMITTING TRACT (NTT), caused a failure of fruit dehiscence in Arabidopsis. We identified ntt-3D, in which the 35S enhancer was inserted adjacent to AT3G-57670, from our activation tagged mutant library. ntt-3D mutants showed serrated leaves, short siliques, and indehiscence phenotypes. NTT-overexpressing plants largely phenocopied the ntt-3D plants. As the proximate cause of the indeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Previous studies show that AtWIP2/NTT localize in the nucleus (Appelhagen et al ., ) or in both the nucleus and cytoplasm (Chung et al ., ). Additionally, AtWIP2 forms a homodimer outside of the nucleus and functions mainly as a transcriptional activator (Marsch‐Martinez et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies show that AtWIP2/NTT localize in the nucleus (Appelhagen et al ., ) or in both the nucleus and cytoplasm (Chung et al ., ). Additionally, AtWIP2 forms a homodimer outside of the nucleus and functions mainly as a transcriptional activator (Marsch‐Martinez et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, similar phenotypes related to cotyledons and seedling growth were found in GhWIP2OE Arabidopsis and AtWIP2/NTT gain‐of‐function plants. Both of them showed narrow cotyledons and stunted growth (Chung et al ., ) (Figs S6, S7). This means GhWIP2 and AtWIP2/NTT may share similar function.…”
Section: Discussionmentioning
confidence: 94%
“…Plant‐specific DOF‐ type (DNA‐binding with one finger) transcription factors control various biological processes, of which the Arabidopsis dof4.2 mutant showed increased silique length and seed yield (Zou et al , ). The Arabidopsis NO TRANSMITTING TRACT ( NTT ) gene encodes a C2H2/C2HC zinc finger transcription factor that is specifically expressed in the transmitting tract and responsible for replum development (Chung et al , ). NTT loss function in Arabidopsis leads to reduced male fertility, seed set and silique length (Marsch‐Martínez et al , ).…”
Section: Transcription Factorsmentioning
confidence: 99%
“…Even conserved partial valve tissues developed into valve margin-like tissues (including lignified and dehiscence zone-like cell types), or formed into narrow files of replum cells that resemble those in the valve margin. Furthermore, seed development was reduced through valve elongation restrained after fertilization, especially in the basal part of the fruit due to a lack of coordinated growth of the fruit tissues, and resulted in yield failure [10, 12, 1719]. In this study, overexpression of BnLATE resulted in less lignification in the replum, valve layer and dehiscence zone of yellowing silique in B .…”
Section: Discussionmentioning
confidence: 84%
“…Recently, Crawford, Ditta [16] reported that NO TRANSMITTING TRACT ( NTT ), a C 2 H 2 /C 2 HC-type zinc finger protein, plays a role in the differentiation of the transmitting tract in the carpels of Arabidopsis thaliana . Chung, Lee [17] showed that an activation-tagged allele of NTT ( ntt-3D) exhibited a silique indehiscence phenotype, and lacked lignified cells in the valve margin. However, these mutants, which were silique shattering-resistant, had reduced valve elongation after fertilization and substantially reduced seed development, especially in the basal part of the fruit due to a lack of coordinated growth of the fruit tissues, resulted in crop failure [10, 12, 1719].…”
Section: Introductionmentioning
confidence: 99%